Wormlike emulsion droplets - Jatin Abacousnac; Wenjun Chen; Jasna Brujic; David G. Grier (Physical Review Research)
Forming an interface between immiscible fluids incurs a free-energy cost that usually favors minimizing the interfacial area. An emulsion droplet of fixed volume therefore tends to form a sphere, and pairs of droplets tend to coalesce. Surfactant molecules adsorbed to the droplets' surfaces stabilize emulsions by providing a kinetic barrier to coalescence. Here, we show that the pressure exerted by bound surfactant molecules also competes with the droplet's intrinsic surface tension and can reverse the sign of the overall surface free energy. The onset of negative surface tension favors maximizing surface area and therefore favors elongation into a wormlike morphology. Analyzing this system in the Gibbs grand canonical ensemble reveals a phase transition between spherical and wormlike emulsions that is governed by the chemical potential of surfactant molecules in solution. Predictions based on this model agree with the observed behavior of an experimental model system composed of lipid-stabilized silicone oil droplets in an aqueous surfactant solution.